Histopathologic findings on indication renal allograft biopsies after recovery from acute COVID‐19. Issue 12 (1st October 2021) - Basic‐Jukic, Nikolina; Coric, Marijana; Bulimbasic, Stela; Dika, Zivka; Juric, Ivana; Furic‐Cunko, Vesna; Katalinic, Lea; Kos, Jelena; Fistrek, Margareta; Kastelan, Zeljko; Jelakovic, Bojan
Abstract: Current knowledge on histopathological changes occurring after COVID‐19 in transplanted kidneys is limited. Herein, we present renal allograft pathology findings in patients recovered from COVID‐19. Six patients underwent indication biopsy, and one required allograft nephrectomy after acute COVID‐19. Demographic data, clinical characteristics, and laboratory findings were recorded. The histopathological analysis included light microscopy, immunostaining, and electron microscopy. Five patients were hospitalized for acute COVID‐19, and all were diagnosed with imaging‐confirmed pneumonia, one requiring mechanical ventilation, and two requiring dialysis. Two patients had mild form. Histopathologic examination of renal allograft specimens revealed collapsing, perihilar, tip‐lesion and secondary FSGS in one patient each. One patient had borderline acute cellular rejection, and two had chronic antibody‐mediated rejection. Histopathologic changes of glomerular tufts were accompanied by acute tubular injury in four patients. None of our patients had signs of viral inclusions in kidney cells. One patient died and one remained dialysis‐dependent after the good initial response to treatment. Patients with collapsing and perihilar FSGS had further progression of their chronic allograft nephropathy still without need for dialysis. In conclusion, diverse kidney pathology may be found in SARS‐CoV‐2–infected renal transplant patients. It seems that viral infection may affect the immune system with triggering of glomerular diseases, while the acute tubular injury is of multifactorial etiology. Direct viral effect is less likely.